Trasmission of glioma from multiple organ donor to pancreas recipient Giovanni - Marchini, Giovanni Scala; Torricelli, Fábio César Miranda; Kim, Nam Jin; Genzini, Tércio; Miranda, Marcelo Perosa de (Revista de Medicina, 2006)
INTRODUCTION: The disparity between the supply of and the demand fortrans plantable organs has led to an acceptance of donors with primary central nervous system(CNS) tumors. PURPOSE: Face the rarity, the authors report the case of a patient who developed a glioma on a pancreatic graft received from a donor with a malignant glioma as cause of brain death. CASE REPORT: A 11-years-old white female who had died in a local hospital from a malignant glioma was the organ donor. She had been submitted to 4 craniotomies to resect tumoral mass. By the time of organ retrieval, no intra-abdominal or intra-thoracic abnormalities were noticed. Heart, liver, one kidney and pancreas were used for transplant in different recipients. One kidney was not used due to anatomical problems.A pancreas transplant alone was performed in a 21-years-old male, diabetic for 19 years.Postoperative recovery was uneventful and patient was discharged insulin-free. Four months later the patient developed a pancreatic mass and was submitted to graft pancreatectomy.Histology confirmed the same malignant glioma of the donor. Currently the patient has been strictly followed, on his 12th month post-transplant, with a good clinical evolution, off immunosupression and again on insulin, without signs of malignancy.